PAYMENT SYSTEM DEVELOPMENT IN INDONESIA - Soegoto, Herman; Apsarini, Felicia; Supandi, Agus (Jurnal Riset Bisnis dan Manajemen, 2024)
The objective of this paper is to provide insight into the payment system transformation in Indonesia. The discussion method uses quantitative descriptive analysis related to the payment system and development, as well as digital payment statistics in Indonesia. To predict the number of digital payment users after 2022, we use quantitative management tools for Windows based on the time series data in the past years. According to the data and analysis, the number of digital payment users in Indonesia continuously experienced a linearly increasing trend each year. Currently, there has been a shift in people’s behaviour from using a paper-based instrument previously to using digital payment as a payment method. This shift is in line with the growth of information technology and change in the business model, followed by the new regulations and policies issued by the Indonesia Central Bank.